What is Agile? - Stellman, Andrew; Greene, Jennifer 1971- ([O'Reilly Media], 2017)
Agile has become popular with software teams because the ones that have "gone agile" often talk about the great results they get. The software they build is better, which makes a big difference to them and their users. Not only that, but when agile teams are effective, they have a much better time at work. Things are more relaxed, and the working environment is a lot more enjoyable. Learn why software teams--and other teams at companies--are embracing agile